Peningkatan Hasil Belajar PAK melalui Model PBL Berbasis Canva di SDN Saloo Hilina’a - Agustinus Zebua; Ansel Joko Prayitno (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This research was motivated by the low learning outcomes of students in Catholic Religious Education (PAK) at SDN Saloo Hilina’a, which is attributed to the lack of innovative learning media used by educators. The study, titled